Ювелірна форма з Ходосівського поселення волинцевської культури - Комар, О.В. (Археологія і давня історія України, 2021)
У публікації вводяться в науковий обіг матеріали зі споруди волинцевської культури другої половини VIII ст. зі знахідкою стулки форми для виготовлення легкоплавких прикрас-нашивок кола Бернашівки. Casting molds for making small ornaments of lead
or tin alloys were found in different parts of the East
Europe in the areas of various archaeological cultures.
This simple technology and simple shapes of products
were in use by many peoples since 3rd till 10th century
and perhaps even earlier. Lead castings and stone
molds for their manufacture attracted the attention of
researchers of Early Slavic archaeology since discovery
of the Velyki Budky hoard (1981) and Bernashivka
workshop (1990).
The obvious problem was the chronological and geographic
lacuna between the Slavic Bernashivka type
ornaments (6th—7th centuries) and ornaments of the
Kamno-Rõuge type (8th—10th centuries) from the Eastern
Baltic region. Several versions explaining the similarity
of finds from the northern and southern areas
have been proposed: common substrate, population migrations,
imitation of some fashion etc. In recent years
two molds for some ornaments of the Kamno-Rõuge
type have been discovered at the Romny culture hillforts
(Sverdlovske 1, Vorkhol II), which demonstrated
the lasting of the tradition in the south until the
10th century.
A problem of the upper limit for existence of the
Bernashivka type ornaments can be clarified using
the mold find from Khodosivka settlement. The mold
was discovered by expedition of E. O. Petrovska in
1976 during a survey along the left edge of the Gley
ravine (Kozakiv ravine) near the Khodosivka hillfort.
It was found in remaining part of a pit dwelling in context
with fragments of hand-made and wheel-made
pots of the Volyntsevo culture. The object dates back
to the second half of the 8th century — early 9th century.
Negatives of ornaments are carved on both sides
of the mold. A diamond-shaped patch carved on the
main side. On the reverse side the negatives of round
plaques are carved and probably loops for attaching
the same plaques. There is also circular decoration
presents, probably, of a circular pendant. The closest
analogies to such decorations were found in the Bernashivka
workshop, and also at the molds from the
Lower Danube region. Products from the Khodosivka
mold look quite archaic and simple in comparing to
gold and silver jewelry from hoards of the Volyntsevo
culture. Such production was undoubtedly the part of
nonprofessional home craft.